Personal agency the metaphysics of mind and action - Lowe, E. J. (E. Jonathan) (Oxford : Oxford University Press, 2008)
E.J. Lowe defends a common-sense view of ourselves as free agents, capable of bringing about changes in the world through the choices we make, rather than being caused to act as we do by factors external to our will.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Agent (Philosophy); Choice (Psychology); Free will and determinism